基于虚拟样机的隔膜泵动态特性分析 - 刘杰; 李朝峰; 闻邦椿; 王磊 (Jixie chuandong)
The virtual prototype of the diaphragm pump was presented through Pro-E and ADAMS. It can provide all the kinematics and dynamic parameters. The way to study the dynamic properties and the basis of the finite analysis of the diaphragm pump was given. The way to optimize the parameters and develop deeply was provided.